2019
DOI: 10.1016/j.devcel.2019.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Compensation Promotes Liver Regeneration

Abstract: Highlights d Liver regeneration is characterized by distinct patterns of gene expression d Uhrf1 loss in hepatocytes enhances liver regeneration despite DNA hypomethylation d H3K27me3 accumulates on hypomethylated transposons in Uhrf1-deficient livers d Promoters of proregenerative genes lose H3K27me3, facilitating their activation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 87 publications
(111 reference statements)
9
67
1
1
Order By: Relevance
“…These results indicate that removal of repressive marks 5mC and H3K27me3 as well as injury-induced changes of H3K4me3, which is associated with active promoters and hypomethylated promoters are the first step for the initial reprogramming of RPE. In accordance with the reduction of 5mC, we observed significant downregulation of DNMTs and the critical regulator of DNA methylation uhrf1, a factor that is associated with liver regeneration and redistribution of H3K27me3 from promoters to transposons [98]. Our results obtained at 6 hPR in t-rRPE partially recapitulate the results observed during fin regeneration in zebrafish, where the levels of 5mC and 5hmC were transiently reduced at 24 hours postamputation (hpa) in the blastema cells, and such reduction was also independent of proliferation [37].…”
Section: Discussionsupporting
confidence: 80%
“…These results indicate that removal of repressive marks 5mC and H3K27me3 as well as injury-induced changes of H3K4me3, which is associated with active promoters and hypomethylated promoters are the first step for the initial reprogramming of RPE. In accordance with the reduction of 5mC, we observed significant downregulation of DNMTs and the critical regulator of DNA methylation uhrf1, a factor that is associated with liver regeneration and redistribution of H3K27me3 from promoters to transposons [98]. Our results obtained at 6 hPR in t-rRPE partially recapitulate the results observed during fin regeneration in zebrafish, where the levels of 5mC and 5hmC were transiently reduced at 24 hours postamputation (hpa) in the blastema cells, and such reduction was also independent of proliferation [37].…”
Section: Discussionsupporting
confidence: 80%
“…These results indicate that removal of repressive marks 5mC and H3K27me3 as well as injury-induced changes of H3K4me3, which is associated with active promoters and hypomethylated promoters are the first step for the initial reprogramming of RPE. In accordance with the reduction of 5mC, we observed significant downregulation of DNMTs and the critical regulator of DNA methylation uhrf1, a factor that is associated with liver regeneration and redistribution of H3K27me3 from promoters to transposons [83]. Our results obtained at 6 hPR in t-rRPE, partially recapitulate the results observed during fin regeneration in zebrafish where the levels of 5mC and 5hmC were transiently reduced at 24 hours post-amputation (hpa) in the blastema cells, and such reduction was also independent of proliferation [37].…”
Section: Discussionsupporting
confidence: 80%
“…Heat maps analysis were generated using Easeq software. The following published ChIP-seq datasets were used: GSM2339529 (SETDB1 ChIP-Seq in Hepa 1.6 cells; Mus musculus; ChIP-Seq); GSM2339528 (KAP1 ChIP-Seq inHepa 1.6 cells; Mus musculus; ChIP-Seq); GSM2339536 (Total input Hepa 1.6 cells; Mus musculus; ChIP-Seq) (Kauzlaric et al, 2017); GSM3753284 (baseline WT H3K9me3); GSM3753283 (input WT H3K9me3) (Wang et al, 2019); GSM3679089 (WT H3K27Ac) and GSM3679121 (WT H3K4me1) (Praestholm et al, 2020).After re-analyzing all ChIPseqs using the same parameters as Zfp125 ChIP-seq, BED files were generated and used for heat map studies.…”
Section: Methodsmentioning
confidence: 99%
“…KRAB-ZFPs promote formation of heterochromatin by attracting co-repressors (Frietze et al, 2010;Seah et al, 2019;Sripathy et al, 2006). To test if this was the case with Zfp125, we used a published adult mouse liver dataset of the heterochromatin marker H3K9me3-ChIP-seq (Wang et al, 2019) and found a ~50% overlap with Zfp125 ChIP peaks ( Fig. 4A).…”
Section: Zfp125 Is a Transcriptional Repressor Of Metabolically Relatmentioning
confidence: 99%